1983
DOI: 10.1111/j.1651-2227.1983.tb09731.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in Diabetic Children and Adolescents

Abstract: In order to establish the general prevalence of peripheral neuropathy in diabetic children and adolescents, median motor and sensory conduction velocities and the peroneal motor conduction velocity were registered in 161 unselected diabetic children and adolescents and 55 healthy controls. The influence of the duration and the balance of diabetes on the results was analysed in the diabetic group. In the controls the age correlated positively with the median motor and sensory conduction velocity, but not with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 18 publications
(1 reference statement)
6
8
1
Order By: Relevance
“…Our observation that the motor nerves of the lower extremities are most often affected in adolescents with diabetes is supported by previous data (2,17), although diabetes also affects less myelinated sensory nerve fibers early in the course of the disease (1). The finding that the adolescent patients with distal DP also had parasympathetic nerve dysfunction is in line with previous results in adult patients (3,19) and supports the observation of distal neural damage in diabetic polyneuropathy.…”
Section: Table 3-h-reflex Latency Difference (Milliseconds) In the Tisupporting
confidence: 80%
See 1 more Smart Citation
“…Our observation that the motor nerves of the lower extremities are most often affected in adolescents with diabetes is supported by previous data (2,17), although diabetes also affects less myelinated sensory nerve fibers early in the course of the disease (1). The finding that the adolescent patients with distal DP also had parasympathetic nerve dysfunction is in line with previous results in adult patients (3,19) and supports the observation of distal neural damage in diabetic polyneuropathy.…”
Section: Table 3-h-reflex Latency Difference (Milliseconds) In the Tisupporting
confidence: 80%
“…The finding that the adolescent patients with distal DP also had parasympathetic nerve dysfunction is in line with previous results in adult patients (3,19) and supports the observation of distal neural damage in diabetic polyneuropathy. The fact that only a few of the adolescent patients had signs or symptoms of distal nerve dysfunction is in accordance with some previous reports (2,17) showing that only ϳ4% of the children or adolescent patients with type 1 diabetes had symptoms or signs consistent with clinical neuropathy. However, abnormal deep tendon reflexes and signs of DP are already detectable in one-fifth of all young and otherwise healthy adult diabetic patients (3).…”
Section: Table 3-h-reflex Latency Difference (Milliseconds) In the Tisupporting
confidence: 78%
“…The greatest impairment was found in peroneal motor conduction velocity: 49 patients (30%) had an abnormal value. There was a strong correlation between the duration of diabetes and peroneal conduction veloc ity impairment [ 17], According to our present and pre vious studies [21], it is noteworthy that we found auto nomic nervous system dysfunction in a significant pro portion of the examined diabetic children compared to the control group. This suggests the more frequent occur rence of subclinical signs referring to the early distur bance of the autonomic nervous system in childhood diabetes, in contrast with peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, some authors recorded the fre quency of abnormal motor nerve conduction as a subclinical sign of peripheral (somatic) neuropathy in about 10% [1], and others in 36% [4], In a study by Kaar et al [17], the median motor and sensory conduction veloci ties and peroneal motor conduction velocity were regis tered in 161 unselected diabetic children and adoles cents. The greatest impairment was found in peroneal motor conduction velocity: 49 patients (30%) had an abnormal value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation